Controle de estoques de sal: uma inovação da quantificação e no gerenciamento dos recursos naturais da indústria mineral - Medeiros Júnior, Eurípedes de (2011)
The strengthening of the domestic industry in Brazil required the modernization, mechanization and expansion of salt production. Thereafter the production of sea salt started to be made in a process of continuous flow, where the product is constantly stored in yards, with daily movements in and out of salt. Thus far, the major bottleneck found in this production process is the control of production, because due to the large amount produced and variety of losses existing in the various stages of production there are not a regulated and safe way to control inventories with accuracy and speed demanded. In a typical case with a salt marsh company of Rio Grande do Norte state, salt produced is stored in two open courtyards and inventory control of salt made by carrying input / output relationship of salt in each storage yard. This work developed a conceptual model of inventory control, based on topography, adopting surveys into one of the courtyards of the company. There were 25 biweekly survey measurements over a year book to generate digital models representing the stock. For each measurement, results were compared with the values of inventory accounting provided by the salt marsh in order to identify existing losses and mark out the sales department on the actual stock available at each measurement date. Inventories calculated by the model indicated losses of 6,349 tonnes for the period of one year book and 3,279 tonnes for the period between harvests, when compared to the accounting control